Legal Insights on Symbolism in Traditional Architecture: Protecting Batam’s “Kampung Tua” - Lie, Cindie; Royce, Charles; Rahman, Maria Puteri; Istiqomah, Nurul; Aurelia, Jennifer; Disemadi, Hari Sutra (Journal of Judicial Review, 2024)
In today’s rapidly modernizing world, traditional architecture often faces threats from swift development and urbanization. Protecting traditional architecture is not merely about preserving physical structures; it is about understanding and maintaining the cultural values embedded within them. By employing an empirical juridical method that combines juridical, conceptual, and ethnographic approaches, this research seeks to explore the philosophical, historical, and cultural values inherent in the traditional Malay architecture of Kampung Tua in Batam City. Additionally, it aims to analyze the relevance and applicability of intellectual property concepts within the context of local communal identity. The findings reveal that while traditional Malay architecture has been recognized as part of communal intellectual property, its legal protection remains inadequate. Proper inventory, documentation, and official recognition are necessary to strengthen legal protection, with collaboration between the government, indigenous communities, and academics being crucial to keeping this cultural heritage alive.